Evaluation of a low-resource soy protein production method and its products - Gulkirpik, Ece; Donnelly, Annette; Nowakunda, Kephas; Liu, Keshun; Andrade Laborde, Juan E. (Frontiers in Nutrition, 2023)
One key approach to achieve zero hunger in Sub-Saharan Africa (SSA) is to develop sustainable, affordable, and green technologies to process nutritious food products from locally available sources. Soybeans are an inexpensive source of high-quality protein that may help reduce undernutrition, but it is underutilized for human consumption. This research evaluated the feasibility of a low-cost method developed initially at the United States Department of Agriculture to produce soy protein concentrate (SPC) from mechanically pressed soy cake and thus create a more valuable ingredient to improve protein intake in SSA. The method was initially tested in the bench scale to assess process parameters. Raw ingredients comprised defatted soy flour (DSF), defatted toasted soy flour (DTSF), low-fat soy flour (LFSF1) (8% oil), and LFSF2 (13% oil). Flours were mixed with water (1:10 w/v) at two temperatures (22 or 60°C) for two durations (30 or 60 min). After centrifugation, supernatants were decanted, and pellets were dried at 60°C for 2.5 h. Larger batches (350 g) of LFSF1 were used to examine the scalability of this method. At this level, protein, oil, crude fiber, ash, and phytic acid contents were measured. Thiobarbituric acid reactive species (TBARS), hexanal concentration and peroxide value were measured in SPC meal and oil to evaluate oxidative status. Amino acid profiles, in vitro protein digestibility, and protein digestibility corrected amino acid score (PDCAAS) were determined to assess protein quality. Bench scale results showed accumulation of protein (1.5-fold higher) and reduction of oxidative markers and phytic acid to almost half their initial values. Similarly, the large-scale production trials showed high batch-to-batch replicability and 1.3-fold protein increase from initial material (48%). The SPC also showed reductions in peroxide value (53%), TBARS (75%), and hexanal (32%) from the starting material. SPC's in vitro protein digestibility was higher than the starting material. The proposed low-resource method results in an SPC with improved nutritional quality, higher oxidative stability, and lower antinutrient content, which enhances its use in food-to-food fortification for human consumption and is thus amenable to address protein quantity and quality gaps among vulnerable populations in SSA.